(untitled) (Revista científica Olimpia, 2021)
The artistic gymnastics is a sport of early specialization where the physical preparation and technique plays an important paper. To educate these two elements proportionally in the same address in the initiation stage guarantees future results and it is a challenge in each trainer’s work. However, previous studies carried out by the authors detected deficiencies in the teaching of the physical and technical abilities of the gymnasts, category 7-8 years, evidenced in the systematic of the trainings. Assisting to this problem, the present article exposes the relating ones theoretical of the teaching process and learning in the category mentioned previously, from the positions of different authors and the opinions that approach on the topic in study.